Determining the efficiency of carbonaceous adsorbents in removing chromium (VI) from aqueous solution - M., Parichehre; F., Sadeghzadeh; B., Jalili; M. A., Bahmanyar; A. W., Samsuri (Water and Wastewater Consulting Engineers, 2023)
The increase of various industries and the growth of the earth's population have caused various types of contamination in the environment. Anionic contaminants are one of the most important contaminants in water, which have many risks to human health and living organisms and also have many important environmental risks. Therefore, it is important to modify these resources. Studies showed that the use of biochar and metal-coated biochar effectively leads to the removal of a significant amount of contaminants from water and soil, but so far, the effect of carbon-metal composite on the removal of contaminants, especially anionic contaminants, has not been comprehensively investigated. In this research, the effect of biochar, metal-coated biochar and biochar-metal composite on the removal of chromium from water was investigated. Metal-coated biochars and various biochar-metal composites were prepared from the combination of metals (copper, iron and aluminum) with agricultural residues (rice straw) in raw form or as a biochar. The samples included Biochar, Copper-coated biochar, Aluminum-coated biochar, Ironcoated biochar, Copper composite, Aluminum composite, and Iron composite. In the first stage, the optimal conditions for contaminant removal were investigated, then an optimal amount of adsorbents and contaminant with a concentration of 20 mg/L and pH=6 were combined and shaken for three hours. until they reached equilibrium. After centrifugation and filtration, the final concentration of the contaminant was read and the chromium removal percentage was calculated. The results of the present research showed that the application of iron composite and iron-coated biochar could remove 90.32 and 93.71 percent of chromium pollutant from the aqueous solution, respectively. Therefore, the use of these adsorbents can remediate chromium-contaminated water.